BRAND ASSOCIATION PERGURUAN TINGGI JAWA BARAT MENGHADAPI PERSAINGAN MASYARAKAT EKONOMI ASEAN (MEA) DAN DUNIA - Gunawan, Rahmat (JURNAL VISIONIDA, 2017)
The condition of State and Private Universities in Indonesia, especially West Java, is connected with the condition of universities in the world is still very alarming. PTN and PTS rankings in Indonesia and West Java in particular are still far from expectations. West Java Higher Education Position for world level still not able to occupy the rank of 100 magnitude. Still far from the top 50 positions. Even to the level of Asia although not many PT in Indonesia especially West Java which is able to occupy the top 50 rankings. In ASEAN only UI is able to rank 6th ASEAN. The others are far from expectations. The phenomenon of such problems need to be explored and sought by the solution so that Indonesian universities in West Java can advance in the competition among PT in the world, especially ASEAN and Asia so as to increase the competitiveness of Indonesian nation in the competition of nations in the world.Keywords: Universities, Competitiveness, Asean Economic Community